Durability of staining and glazing on a hybrid ceramics after the three-body wear: Hybrid ceramic stain durability - Tribst, João P.M. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; Werner, Arie; Anami, Lilian C.; Bottino, Marco A. [UNESP]; Kleverlaan, Cornelis J. (Elsevier, 2020)
Hybrid ceramic is a promising material for monolithic restorations that could require an individualization through the extrinsic staining to improve aesthetics. Due to the possibilities to treat this ceramic prior to staining, this study evaluated the wear resistance of surface treatments prior to staining and glazing a hybrid ceramic. Thirty-two specimens (Vita Enamic) were divided into 8 groups according to the surface treatment prior to the staining (Polishing: Pol, Acid etching: Ac, Sandblasting with Al2O3: Sd or Self-etching silane: Ses) and glaze application (with: gl or without: gl). The specimens were submitted to the ACTA wear machine simulating the presence of food bolus and antagonist. The wear rate of the stain was determined after 7 intervals of 20,000 cycles, using a profilometer. The surface before and after staining, and after wear were inspected using Scanning Electron Microscopy (SEM). The rates were analyzed using three-way ANOVA and Tukey test. The wear was affected by surface treatment, glaze application and number of cycles (p < 0.001). 100% of the staining was removed after 20,000 cycles for Pol, 40,000 for Pol + gl, 60,000 for Ses + gl, 80,000 for Ac, 100,000 for Sd and Ses, 120,000 for Ac + gl and 140,000 for Sd + gl. SEM showed similar worn surfaces. Sandblasting followed by glaze application was the most durable treatment to maintain the external staining on the hybrid ceramic surface when subjected to three-body wear.
Keywords: ACTA wear Machine; Hybrid ceramic; Surface treatments; Wear depth and wear volume; Wear facet